Preparation of instant sago noodles fortified with catfish protein concentrat as a high nutrition food with different formulations - Fadli Hermanto Hermanto; Syahrul '; Dahlia ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was intended to abtain the best formulation of instant sagonoodles fortified with catfish protein concentrat. Three types of sago noodles werepreparet with different formulation: Sago noodles-1: Roasted sago flour (41,28%),catfish protein concentrat (4,13%), soybean flour (4,13%), skim milk (10,32%),sodium trypolipospat (0,10%), sugar flour (6,19%), phyto-oil (2,06%), salt(0,83%), water (30,96%), sago noodles-2: Roasted sago flour (43,06%), catfishprotein concentrat (4,31%), carrot extract (32,29%), skim milk (10,76%), sodiumtrypolipospat (0,11%), sugar flour (6,46%), phyto-oil (2,15%), salt (0,86%), andsago noodles-3: Roasted sago flour (43,06%), catfish protein concentat (4,31%),spinach extract (32,29%), skim milk (10,76%), sodium trypolipospat (0,11%),sugar flour (6,46%), phyto-oil (2,15%), salt (0,86%). All sago noodles wasevaluated for sensory quality, protein, fat, ash, moisture, carbohydrate, vitamin A,and total bacterial count. The results showed that the sago noodles-3 was the mostpreferable product. Protein, fat, ash, moisture, carbohydrate, vitamin A, and totalbacterial count, for the sago noodles-1 was 7,47%, 5,05%, 2,03%, 4,30%, 84,36%,125 A IU, and 5,9 x 102 bacterial/gram respectively, sago noodles-2 was 5,60%,2,50%, 2,01%, 3,29%, 83,72%, 94,2 IU, and 5,4 x 102 bacterial/gram respectivelyand sago noodles-3 was 5,75%, 4,75%, 1,85%, 3,46%, 83,16%, 123 IU, and 5,8 x102 bacterial/gram respectively.Keyword: sago noodles, instant , catfish protein concentrate, carrot extract,spinach extract.